Contribution to diagnostics/prognostics of tuberculosis in children. I. New methods of assaying zinc and simultaneously copper and zinc in diluted sera by flame atomic-absorption spectrometry - Luterotti Svjetlana; Kordić Tončica Vukman; Dodig Slavica (Acta Pharmaceutica)
In an attempt to provide a reliable status of metal ions in children, new methods of analysis of children’s sera are proposed. New flame atomic-absorption spectrometric (FAAS) methods are simple, cost- and time-effective and, above all, labor-, reagent- and sample-saving. Two methods were suggested: method A for simultaneous determination of Cu and Zn from 5-fold diluted sera, and method B, for assaying zinc alone in 10-fold diluted samples. Both methods are based on a single-step sample pretreatment (deproteinization with 3 mol dm–3 HCl). Method A uses a single-step calibration with a mixed standard. The main advantage of method B is an additional reduction in sample consumption. Both methods were fully validated against reference methods. Accuracy, sensitivity and precision have proven them to be comparable to the reference methods in terms of analytical performance, and applicable to analyses of children’s sera.